Non-alcoholic fatty liver disease in obese and overweight children - Akhter, Romana; Begum, Suraiya; Alam, Farzana; Shyamaly, Kohinoor Jahan; Tithi, Baraka Badrudduja; Karim, Mohammad Rezaul (International Journal of Contemporary Pediatrics, 2021)
Background: Childhood obesity is rising alarmingly and approaching an epidemic proportion in many countries. It increases the risk of developing non-communicable disease in adulthood. Non-alcoholic fatty liver disease (NAFLD) is a key co-morbidity associated with obesity and emerged as the leading cause of chronic liver disease in children. This study aimed to see the prevalence of the NAFLD with overweight and obesity among children. Methods: It was a cross sectional study conducted among children aged 5.5 to 18 years attending in the pediatric endocrinology clinic of department of pediatrics, Bangabandhu Sheikh Mujib medical university over a period of 14 months. Children’s weight and height were evaluated and then BMI was calculated for particular age and sex according to center for disease control growth chart. All obese and overweight children were included except those taking systemic steroid, or suffering from genetic, endocrine, liver or renal disease. Patients were advised to do serum alanine aminotransferase (ALT) and ultrasonography of hepatobiliary system. Results: A total of 90 children were enrolled in the study. Among them majority (93.3%) were obese and the rest were overweight (6.7%). Overall, 40% children had NAFLD including 40.5% among the obese and 33.3% among the overweight (p>0.05). Majority (91.6%) had mild NAFLD. Alanine amino transferase (ALT) level was raised significantly among children with NAFLD compared to those without NAFLD (58.3% and 16.7% respectively, p<0.001). Conclusions: More than one-third of the overweight and obese children had NAFLD with a significantly higher level of ALT compared to children without NAFLD. Therefore, NAFLD should be routinely screened among children with increased weight to take timely intervention and prevent further progression of the disease.